HAS THE US POLICY BEEN MORE ANTI-IRANIAN THAN PRO-ARAB WITH THE FALL OF THE SHAH? A HISTORICAL ANALYSIS - Ilmi Dwiastuti (Jurnal Ilmu Sosial Indonesia (JISI), 2020)
AbstractSince the fall of the Shah, the US-Iran relations have changed significantly. During the Shah regime, US-Iran experience a warm relationship through economic and military partnerships, however, it changed since the Iran revolution until today. Iran turned out to be one of the axis of evil during the Bush administration. The fall of the Shah also changes the direction of the foreign policy of the US. It then led to the proposition of whether the US foreign policy has been more anti-Iranian than pro-Arab with the fall of the Shah. This paper seeks to answer this question through historical analysis. It examines the US policy during the Cold War era and the post-Cold War. Therefore, the US policy in the region is not always anti-Iranian than the pro-Arab case. The changed regional architecture influences the priorities of the President of the US at that time to put aside Iran's issue, as it happened on George H.W. Bush, Clinton, and Obama administration. Thus, the characteristic of the leader also heavily influences US posture in Iran, as Bush and Trump's personality and policies are clearly against Iran. However, despite the dynamic relations of the US-Iran, Iran has always been one of the threats for the US interest in the Persian Gulf since the Shah has fallen.